Adiposity and clinical outcomes in East Asian patients with heart failure and preserved ejection fraction. (February 2023) - Seki, Yuko; Obokata, Masaru; Harada, Tomonari; Kagami, Kazuki; Sorimachi, Hidemi; Saito, Yuki; Kato, Toshimitsu; Ishii, Hideki
Abstract: Background: Despite the obesity paradox, visceral adiposity is associated with poor clinical outcomes in patients with heart failure with preserved ejection fraction (HFpEF). However, it remains unclear whether a relationship between visceral fat and clinical outcomes exists in Asian patients with HFpEF, in whom obesity is rare. Methods: Visceral and subcutaneous adipose tissue (VAT and SAT) volume and area were measured using computed tomography (CT) in 196 HFpEF patients. The primary endpoint was a composite of all-cause mortality or HF hospitalization. Results: Participants had a normal body mass index (BMI) (22.5 ± 4.4 kg/m 2 ), and obesity (BMI > 30 kg/m 2 ) was rare (4.6 %). The primary outcome was observed in 64 patients during a median follow-up of 11.6 months. Lower VAT and SAT volumes were associated with underweight and malnutrition. Composite outcomes increased as body weight, BMI, and height-indexed SAT volume and area decreased. Lower height-indexed VAT volume and area were also associated with the outcomes. The height-indexed SAT area provided independent and incremental prognostic value over age, BMI, blood pressure, and creatinine and albumin levels. Conclusions: In lean East Asian patients with HFpEF, a lower VAT volume was associated with poorer clinical outcomes. CT-based assessments of adiposity may provide incremental prognostic value over simple anthropometric indices in lean HFpEF patients.